Structure of mangrove ecosystem in Lubuk Damar Coast, Seruway, Aceh Tamiang - Darmarini, Ananingtyas S; Wardiatno, Yusli; Partono, Tri; Soewardi, Kadarwan; Samosir, Agustinus Mangaratua; Zainuri, M (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Mangrove is an important ecosystem in coastal areas because it is the basis for the formation of food webs and has direct and indirect impacts on aquatic and terrestrial ecosystems. The purpose of this research is to determine the community structure of mangrove vegetation of Lubuk Damar, Seruway, Aceh Tamiang. The study was conducted in August 2017. The method used a quadratic transect that was pulled straight from the coastline to the mainland. The results found 10 types of mangrove vegetation consisting of A. alba, B. parviflora, B. sexangula, Soneratia alba, R. apiculata, Acrostichum aureum, Aegiceras floridum, E. agallocha, X. granatum, and Acanthus ilicifolius. Mangrove species with the highest percentage are in the A. floridum species. Important value index the tree phase in the range of 4.75 to 117.91. Lubuk Damar mangrove vegetation is in the damaged category. However, the number of saplings and seedlings was found to have a high density so that the ecosystem has the potential to regenerate naturally.